2017
DOI: 10.5539/jel.v6n3p312
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Job Statisfaction Levels and Work-Family Conflicts of Physical Education Teachers

Abstract: Study aims to examine the relationship between perceived job satisfaction levels and work-family conflicts of the physical education teachers. Research group consists of 154 volunteer physical education teachers that work full time in governmental institutions in Kirşehir city and its counties. To acquire the job satisfaction datum; the Minnesota job satisfaction Scale, developed by Weiss, Dawis, England and Lofquist (1967) and adapted to Turkish version by Baycan (1985), was used. For acquiring the work-famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…This suggested that primary and secondary school principals’ work-family conflict directly related to work engagement and also indirectly related to work engagement through job satisfaction. Meanwhile, the results also support those of previous studies reporting that work-family conflict is an important factor affecting teachers’ job satisfaction ( Erdamar and Demirel, 2016 ; Ulucan, 2017 ), and job satisfaction was positively correlated with work engagement ( Taghipour and Dezfuli, 2013 ; Huang et al, 2016 ; Wang et al, 2017 ; Park and Johnson, 2019 ). Following the conservation of resources theory, when individuals devote resources to coping with the conflict between work and family, then the resources available for other things will decrease.…”
Section: Discussionsupporting
confidence: 89%
“…This suggested that primary and secondary school principals’ work-family conflict directly related to work engagement and also indirectly related to work engagement through job satisfaction. Meanwhile, the results also support those of previous studies reporting that work-family conflict is an important factor affecting teachers’ job satisfaction ( Erdamar and Demirel, 2016 ; Ulucan, 2017 ), and job satisfaction was positively correlated with work engagement ( Taghipour and Dezfuli, 2013 ; Huang et al, 2016 ; Wang et al, 2017 ; Park and Johnson, 2019 ). Following the conservation of resources theory, when individuals devote resources to coping with the conflict between work and family, then the resources available for other things will decrease.…”
Section: Discussionsupporting
confidence: 89%
“…Gender is highly correlated to personality traits, style tendency and leadership style. Education on the other hand is highly correlated to job satisfaction, personality traits, style tendency and job satisfaction.Study conducted by Ulucan (2017) pointed out that job satisfaction and work-family conflicts exhibited by physical education teachers are not significantly related each other. This means that the entities are independent and may not have direct effects against each other.…”
Section: Table 2 Personality Traits Of the Respondentsmentioning
confidence: 92%
“…The higher the score, the higher the conflict. The Cronbach Alpha for work-to-family conflict is 0.73 and that of the family-to-work conflict scale is 0.80 (Ulucan, 2017).…”
Section: Constructs Instruments and Interpretation Work-family Conflict Scalementioning
confidence: 94%